2018
DOI: 10.1111/1365-2745.12935
|View full text |Cite
|
Sign up to set email alerts
|

The structure of plant spatial association networks is linked to plant diversity in global drylands

Abstract: 1. Despite commonly used to unveil the complex structure of interactions within ecological communities and their value to assess their resilience against external disturbances, network analyses have seldom been applied in plant communities. We evaluated how plant-plant spatial association networks vary in global drylands, and assessed whether network structure was related to plant diversity in these ecosystems. 2. We surveyed 185 dryland ecosystems from all continents except Antarctica and built networks using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 71 publications
3
34
0
Order By: Relevance
“…Our observed network was composed of 19 plant species linked by 36 associations. This yields a level of connectivity equal to 11%, which is similar to other plant networks, for instance in deserts (Losapio et al., ; Verdù & Valiente‐Banuet, ) and drylands (Saiz et al., ), or even similar compared to aquatic food webs (Dunne, Williams, & Martinez, ). Only one plant species was completely isolated from the network, two were less connected whereas three species were more connected to other plant species than expected by chance.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our observed network was composed of 19 plant species linked by 36 associations. This yields a level of connectivity equal to 11%, which is similar to other plant networks, for instance in deserts (Losapio et al., ; Verdù & Valiente‐Banuet, ) and drylands (Saiz et al., ), or even similar compared to aquatic food webs (Dunne, Williams, & Martinez, ). Only one plant species was completely isolated from the network, two were less connected whereas three species were more connected to other plant species than expected by chance.…”
Section: Discussionsupporting
confidence: 65%
“…For instance, facilitation can induce fine‐scale associations (Bruno, Stachowicz, & Bertness, ; Chacon‐Labella, de la Cruz, & Escudero, ; Schöb, Kammer, Kikvidze, Choler, & Veit, ) while competition can reduce them (Durrett & Levin, ; MacArthur & Levins, ; Pescador, Chacon‐Labella, de la Cruz, & Escudero, ; Tilman, ). The structure of plant communities can therefore be seen as a complex network of positive and negative interactions among species (Levine, Bascompte, Adler, & Allesina, ; Losapio, Pugnaire, O'Brien, & Schöb, ; Saiz, Gomez‐Gardeñes, Borda, & Maestre, ; Verdù & Valiente‐Banuet, ). Although this perspective could shed light on the assembly of plant communities, the ecological factors contributing to the formation of these plant networks are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…There are very important differences. Interactions in classic co‐occurrence networks are inferred from the existence of statistically significant spatial covariation in the abundance (or presence) of two species across samples (for plant–plant co‐occurrence networks see Saiz, Alados, & Pueyo, ; Saiz, Gómez‐Gardeñes, Borda, & Maestre, ). One important consequence is that interaction matrices from co‐occurrence networks are symmetric (undirected): if species A “interacts” (or, more properly, covaries spatially) with species B, then B necessarily “interacts” with A.…”
Section: Conceptual Obstacles That May Have Hindered Research On Recrmentioning
confidence: 99%
“…They are threatened by global land‐use and climate changes that may further decrease water availability (D'Odorico, Bhattachan, Davis, Ravi, & Runyan, ). Previous investigations of this database have revealed that abiotic factors such as aridity and pH determine the diversity (Soliveres et al, ; Ulrich et al, ) and spatial distribution (Saiz, Gómez‐Gardeñes, Borda, & Maestre, ) of plant communities, but their effect on SAR has never been investigated. Hence, in this contribution we studied the SAR patterns of perennial plant communities, focusing on the following questions: What is the relative role of different proximate factors (evenness, density spatial aggregation and species pool) in determining SAR patterns? How do proximate factors mediate the effect of aridity and pH on SAR? …”
Section: Introductionmentioning
confidence: 99%